2006
DOI: 10.1104/pp.105.074724
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Plant-Specific Family Gene, ROOT PRIMORDIUM DEFECTIVE 1, Is Required for the Maintenance of Active Cell Proliferation

Abstract: Hypocotyl segments of Arabidopsis (Arabidopsis thaliana) produce adventitious roots in response to exogenously supplied auxin. root primordium defective 1 (rpd1) is a temperature-sensitive mutant isolated on the basis of impairment in this phenomenon. This study describes further phenotypic analysis of the rpd1 mutant and isolation of the RPD1 gene. When adventitious root formation was induced from the rpd1 explants at the restrictive temperature, cell proliferation leading to root promordia formation was init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 59 publications
7
33
0
Order By: Relevance
“…Considering the RNA-binding and RNA-splicing activities of WTF1, it seems likely that most PORR/DUF860 proteins function in organellar RNA metabolism. The one prior report concerning a member of this family, rpd1 in Arabidopsis, is consistent with this view (22). The authors concluded that defects in root and embryo development in rpd1 mutants result from the failure to maintain rapid cell divisions at critical developmental stages.…”
Section: Duf860 Is a Plant-specific Rna-binding Domain Found In A Famsupporting
confidence: 60%
“…Considering the RNA-binding and RNA-splicing activities of WTF1, it seems likely that most PORR/DUF860 proteins function in organellar RNA metabolism. The one prior report concerning a member of this family, rpd1 in Arabidopsis, is consistent with this view (22). The authors concluded that defects in root and embryo development in rpd1 mutants result from the failure to maintain rapid cell divisions at critical developmental stages.…”
Section: Duf860 Is a Plant-specific Rna-binding Domain Found In A Famsupporting
confidence: 60%
“…Histochemical staining of GUS activity was performed basically as described in [10]. When diffuse staining patterns were observed, the concentration of potassium ferricyanide in the staining solution was increased to 3 mM to prevent diffusion of the signal [16].…”
Section: Histochemical Gus Staining and Microscopymentioning
confidence: 99%
“…The root growth defective mutants rgd1, rgd2 and rgd3 became defective after the establishment of the root apical meristem. The ROOT INITIATION DEFECTIVE S (RIDS) gene was identified as the MOR1 / GEM gene encoding a microtubuleassociated protein (Konishi and Sugiyama, 2006). The rid 2-1 mutant is recessive temperature-sensitive mutant of Arabidopsis that was isolated by screening using adventitious root formation as an index phenotype.…”
Section: Genes Asociated With the Adventitious Root Formationmentioning
confidence: 99%